Sensory Processing and Aggressive Behavior in Adults with Autism Spectrum Disorder - Frank van den Boogert; Bram Sizoo; Pascalle Spaan; Sharon Tolstra; Yvonne H. A. Bouman; Witte J. G. Hoogendijk; Sabine J. Roza (Brain Sciences, 2021)
Autism spectrum disorder (ASD) may be accompanied by aggressive behavior and is associated with sensory processing difficulties. The present study aims to investigate the direct association between sensory processing and aggressive behavior in adults with ASD. A total of 101 Dutch adult participants with ASD, treated in outpatient or inpatient facilities, completed the Adolescent/Adult Sensory Profile (AASP), the Reactive-Proactive Aggression Questionnaire (RPQ), and the Aggression Questionnaire—Short Form (AQ-SF). Results revealed that sensory processing difficulties are associated with more aggressive behavior (<semantics>f2=0.25</semantics>), more proactive (<semantics>f2=0.19</semantics>) and reactive aggression (<semantics>f2=0.27</semantics>), more physical (<semantics>f2=0.08</semantics>) and verbal aggression (<semantics>f2=0.13</semantics>), and more anger (<semantics>f2=0.20</semantics>) and hostility (<semantics>f2=0.12</semantics>). Evidence was found for an interaction of the neurological threshold and behavioral response on total aggression and hostility. Participants with higher scores in comparison to the norm group in sensory sensitivity had the highest risk of aggressive behavior. In conclusion, clinical practice may benefit from applying detailed diagnostics on sensory processing difficulties when treating aggressive behavior in adults with ASD.